Inibição do transito gastrintestinal por antipsicoticos : estudo experimental da clozapina - Marques, André Cordeiro (2015)
Clozapine (CLZ) an atypical antipsychotic agent recognized for its efficacy since the early 1960s stills nowadays the drug of choice in treating refractory schizophrenia cases to other antipsychotics. Among the adverse effects of CLZ, constipation, often reported, may progress to bowel obstruction, intestinal necrosis, intraabdominal sepsis and death. This study evaluated the mechanism of action of CLZ on gastrointestinal motility by analyzing the intestinal transit rate (IT) and excretion of fecal pellets in mice. Animals used were Swiss males, weight 25-30g, from the UFC Central Animal Facility and the project approved by the CEPA / UFC (Proc. No. 57/2014). The drugs used were: CLZ (2.5, 5, 10, 20mg/kg p.o.), neostigmine (NEO 1mg /kg i.p.), serotonin (5-HT, 10mg/kg p.o.), alilisotiocianate (AITC 10mg/kg p.o.) , domperidone (DOM 20mg/kg p.o.), L-NAME (80 mg/kg i.p.), naloxone (2 mg/kg s.c.), glibenclamide (5 mg/kg i.p.) and AM251 (1 mg/kg i.p.). Oral administration of CLZ 10 and 20 mg/kg significantly (p <0.05) inhibited IT from the vehicle. Based on the results we decided for the smallest effective dose of CLZ active on intestinal motor function (10mg/kg) for subsequent evaluations. The CLZ inhibited significantly (p <0.05) the excretion of fecal pellets. Pretreatment with naloxone (opioid antagonist), DOM (dopamine antagonist) or with L-NAME (nitric oxide synthase inhibitor) did not inhibit the effect of CLZ (10mg / kg) on gastrointestinal transit. However pretreatment with NEO (anticholinesterasic agent) with 5-HT, with the AITC (TRPA1 agonist), with glyburide (blocker dependent ATP potassium channel) or with AM251 (CB1 antagonist) inhibited significantly (p < 0.05), the effect of CLZ on IT. While the AM 251 inhibited completely the effect of CLZ on IT, it does not alter the effect of CLZ on the excretion of fecal pellets. The effect of CLZ on the gastrointestinal transit and the expulsion of fecal pellets are characteristic of its constipation side effect, consistent with clinical observations in schizophrenic patients treated with CLZ. We can conclude that CLZ inhibits gastrointestinal motor function through a multifactor mechanism of action, involving the modulation of various neurotransmitters among those evaluated in this study points to an inhibitory effect of clozapine on cholinergic and serotoninergic pathways and cation channels TRPA1 and excitatory on the ATP sensitive cation channel and on CB1 receptors.